In Drosophila, RhoGEF2 cooperates with activated Ras in tumorigenesis through a pathway involving Rho1–Rok–Myosin-II and JNK signalling - Peytee Khoo (Disease Models & Mechanisms, 2013)
SUMMARY The Ras oncogene contributes to ∼30% of human cancers, but alone is not sufficient for tumorigenesis. In a Drosophila screen for oncogenes that cooperate with an activated allele of Ras (RasACT) to promote tissue overgrowth and invasion, we identified the GTP exchange factor RhoGEF2, an activator of Rho-family signalling. Here, we show that RhoGEF2 also cooperates with an activated allele of a downstream effector of Ras, Raf (RafGOF). We dissect the downstream pathways through which RhoGEF2 cooperates with RasACT (and RafGOF), and show that RhoGEF2 requires Rho1, but not Rac, for tumorigenesis. Furthermore, of the Rho1 effectors, we show that RhoGEF2 + Ras (Raf)-mediated tumorigenesis requires the Rho kinase (Rok)–Myosin-II pathway, but not Diaphanous, Lim kinase or protein kinase N. The Rho1–Rok–Myosin-II pathway leads to the activation of Jun kinase (JNK), in cooperation with RasACT. Moreover, we show that activation of Rok or Myosin II, using constitutively active transgenes, is sufficient for cooperative tumorigenesis with RasACT, and together with RasACT leads to strong activation of JNK. Our results show that Rok–Myosin-II activity is necessary and sufficient for Ras-mediated tumorigenesis. Our observation that activation of Myosin II, which regulates Filamentous actin (F-actin) contractility without affecting F-actin levels, cooperates with RasACT to promote JNK activation and tumorigenesis, suggests that increased cell contractility is a key factor in tumorigenesis. Furthermore, we show that signalling via the Tumour necrosis factor (TNF; also known as Egr)-ligand–JNK pathway is most likely the predominant pathway that activates JNK upon Rok activation. Overall, our analysis highlights the need for further analysis of the Rok–Myosin-II pathway in cooperation with Ras in human cancers.